Solar water splitting by photovoltaic-electrolysis with a solar-to-hydrogen efficiency over 30% - Jieyang Jia (Nature Portfolio, 2016)
In order to be practical for large-scale deployment, the cost of solar hydrogen generation must be significantly reduced. Here, the authors employ a triple-junction solar cell with two series connected polymer electrolyte membrane electrolysers to achieve solar to hydrogen efficiency of 30%.